Comparative Efficacy of Four Treatments in Patients with Graves’ Disease: a Network Meta-analysis - Ren, Z.; Qin, L.; Wang, J. Q.; Li, Y.; Li, J.; Zhang, R.-G. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Background: The question of which treatment should be preferred for the treatment of Graves’ disease is debatable, and pairwise meta-analyses could not obtain hierarchies of these treatments. Our intention was to integrate the evidence to provide hierarchies of the comparative efficacy of 4 treatments (radioiodine, radioiodine+prednisone, antithyroid drugs and surgery).Methods: We conducted a Bayesian-framework network meta-analysis of randomized controlled trials (RCTs) to compare 4 treatments in patients with Graves’ disease. The eligible RCTs were identified by searching Amed, the British Nursing Index, Embase, PubMed, the Cochrane Central Register of Controlled Trials (CENTRAL), Google scholar, SIGLE, the National Technical Information Service, the National Research Register (UK) and the Current Controlled Trials databases. The data for 2 outcomes (e. g., ophthalmopathy and recurrence) were independently extracted by 2 authors.Results: A total of 4 RCTs were ultimately included. Radioiodine+prednisone therapy showed statistical significance in reducing the incidence of new or deteriorative ophthalmopathy comparing with the other 3 therapies. Compared with radioiodine, therapy with antithyroid drugs therapy as well as surgery significantly decreased the incidence of new or deteriorative ophthalmopathy. Radioiodine therapy significantly reduced the rate of recurrence when compared to therapy with antithyroid drugs or surgery. For decreasing the incidence of new or deteriorative ophthalmopathy, the 4 treatments were ranked as follows: radioiodine+prednisone therapy, therapy with antithyroid drugs, surgery and radioiodine therapy. For reducing the rate of recurrence, 3 treatments were ranked as follows: radioiodine therapy, therapy with antithyroid drugs and surgery.Conclusions: Radioiodine+prednisone therapy might have the least probability of leading to an exacerbation or new appearance of ophthalmopathy, and radioiodine therapy might have the least probability of causing a recurrence.
Keywords: Graves’ disease; network; RCTs; ophthalmopathy; recurrence